PENGARUH STATUS GIZI DAN PEMBERIAN IMUNISASI LENGKAP DENGAN KEJADIAN ISPA DAN BALITA DI PUSKESMAS SIKAKAP KABUPATEN KEPULAUAN MENTAWAI - Hasanalita, Hasanalita; Sari, Putri Permata; Bahri, Serli (Jurnal Kesehatan Saintika Meditory, 2024)
Acute upper respiratory tract infections are caused by viruses. Data on the infant and toddler mortality rate in Indonesia is 18.5% and the mortality rate for children under five (aged 12-59 months) is 8.4%, 14.4% of deaths are caused by pneumonia. In West Sumatra, the death rate for children under five was 84, 19 deaths were caused by pneumonia. In the Mentawai Islands, the death rate for children under five is 5. 1 child's death was caused by pneumonia. Data from the Sikakap Community Health Center was 265 cases of toddlers coughing and having difficulty breathing, 41 cases of toddlers experiencing pneumonia. This type of research is qualitative research, cross sectional design. The research population was all mothers who had toddlers aged 2-3 years. Total sampling technique. The research was carried out from March 3-17 2024. Data was collected using a questionnaire. Bivariate and univariate data analysis was carried out using the Chi Square test. The results of the research showed that there was an influence between nutritional status and the incidence of ARI, with a p value = 0.032 (p<0.05). The incidence of ARI with immunization was found to have a p value = 0.000 (p<0.05). It was concluded that there was a significant relationship between the incidence of ARI with nutritional status and complete immunization. Nutritional status and immunizations influence the incidence of ARI in the Sikakap health center. It is hoped that the Community Health Center can improve education about nutritional status and provide complete basic immunization to mothers.